2013
DOI: 10.1177/230949901302100309
|View full text |Cite
|
Sign up to set email alerts
|

Cephalomedullary Nail versus Sliding Hip Screw for Unstable Intertrochanteric Fractures in Elderly Patients

Abstract: purpose. To compare the short-term ambulatory function of elderly patients after fixation of unstable intertrochanteric fractures with either the AO-ASIF proximal femoral nail anti-rotation (PFNA) device or the dynamic hip screw (DHS). Methods. 63 patients aged ≥60 years underwent fixation for unstable intertrochanteric fractures (AO types A2 and A3) using the PFNA (n=25) or DHS (n=38). The decision for the type of implant used was based on the lead surgeon's preference, according to perceived fracture stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
(24 reference statements)
1
24
1
1
Order By: Relevance
“…Chua et al recently showed that elderly patients who sustained unstable intertrochanteric fractures treated with cephalomedullary nails had better short-term ambulatory function when compared to those treated with sliding hip screws. They had significantly higher Parker Mobility Scores and ability to ambulate independently or with a walking aid 1-year post-operatively [16]. Ziran et al also had similar findings when their IMHS group had better bed transfers, ambulatory ability, and gait distance at discharge [17].…”
Section: Discussionsupporting
confidence: 53%
“…Chua et al recently showed that elderly patients who sustained unstable intertrochanteric fractures treated with cephalomedullary nails had better short-term ambulatory function when compared to those treated with sliding hip screws. They had significantly higher Parker Mobility Scores and ability to ambulate independently or with a walking aid 1-year post-operatively [16]. Ziran et al also had similar findings when their IMHS group had better bed transfers, ambulatory ability, and gait distance at discharge [17].…”
Section: Discussionsupporting
confidence: 53%
“…Statistical Package for the Social Sciences (SPSS) software version 18.0 was used to analyze the data. Continuous data with normal distribution were presented as means and standard deviations, and compared with t test.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients who treated with PFNA underwent cutout due to poor reduction, and 1 patient had avascular necrosis after cutout. The authors found that PFNA was superior in terms of the functional status of the patient and return to pre-fracture mobilization as opposed to our study [29]. Varela-Egocheaga and colleagues conducted a prospective, randomized study of 80 patients with stable intertrochanteric femur fractures aged over 60 years old who were treated with a proximal compression plate or proximal femoral nail.…”
Section: Discussionmentioning
confidence: 65%